Effects of time-restricted eating on body composition and metabolic parameters in overweight and obese women: a systematic review and meta-analysis - Chen, Shiying; Zhang, Xiaotian; Kortas, Jakub; Liu, Haitao (Frontiers in Nutrition, 2025)
BackgroundTime-restricted eating (TRE), a subtype of intermittent fasting, is increasingly explored as a dietary strategy for weight and metabolic management. However, its effects in overweight and obese women remain unclear. This systematic review and meta-analysis aimed to evaluate the impact of TRE on body composition and metabolic parameters in this population.MethodsFollowing PRISMA guidelines and PROSPERO registration (CRD42024595472), randomized controlled trials were retrieved from eight English and Chinese databases up to August 2024. Eligible studies included adult women (≥85% female, BMI ≥ 25 kg/m2) receiving TRE interventions with or without caloric restriction. Quality was assessed using RoB 2.0 and the PEDro scale. Meta-analyses were conducted using Stata 17.0, with evidence certainty graded using GRADE.ResultsThirteen RCTs involving 612 participants were included. TRE significantly reduced body weight (WMD = −1.927 kg, 95% CI: −3.688 to −0.166, p = 0.032) and fasting insulin levels (WMD = −2.120 μU/mL, 95% CI: −4.172 to −0.069, p = 0.043), but showed no significant effects on BMI, fat mass, fat-free mass, visceral fat, blood lipids, glucose, HOMA-IR, or blood pressure (p > 0.05). Subgroup analysis revealed greater weight reduction with TRE compared to conventional diets (p = 0.046), but not versus calorie restriction alone (p = 0.295). No lean mass loss was observed. Four studies reported minor adverse events (e.g., hunger, headache), all self-resolving.ConclusionTRE is effective in reducing body weight and lowering fasting insulin in overweight and obese women, without negatively affecting lean body mass. Compared with traditional calorie-restricted diets, TRE does not yield superior weight loss, suggesting comparable efficacy. TRE demonstrates a favorable safety profile and better adherence, supporting its clinical feasibility. Further trials with larger samples and longer follow-up are needed to clarify TRE’s long-term metabolic effects.Systematic review registrationThe systematic review was registered in PROSPERO. Registration ID: CRD42024595472 URL: https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=459547.